Analisis Urgensi Kompetensi Literasi Digital dalam Mendukung Kemampuan Penulisan Karya Ilmiah Mahasiswa - Salsabila, Nilla Putri; Abidin, Munirul (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose - Technology development is getting faster, especially in the scope of education. The existence of increasingly advanced technology is a challenge to digital literacy competence in students, especially in writing scientific papers. This study aims to reveal the importance of mastering digital literacy in supporting the process of writing scientific papers for students. Method - The researcher used a qualitative descriptive method. The primary data in this study are the results of observations and interviews on the scientific writing habits of postgraduate students at the State Islamic University of Maulana Malik Ibrahim Malang in utilizing digital media. Findings - The result of this study is that the existence of digital literacy is very supportive of student scientific writing. The impact felt by students related to the competence of digital literacy in writing scientific papers is that 1) writing scientific papers becomes better and more effective because they can easily get references through digital journal portals; 2) learning anywhere becomes practical because there is no need to carry many books to move places; 3) improving the ability to find information; 4) improving analytical skills; and 5) improving critical thinking skills.Research Implications - The limitation of this research is that it has not fully revealed the supporting and inhibiting factors of digital literacy in the process of writing student scientific papers.